2015
DOI: 10.1016/j.redox.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Consistent antioxidant and antihypertensive effects of oral sodium nitrite in DOCA-salt hypertension

Abstract: Hypertension is a common disease that includes oxidative stress as a major feature, and oxidative stress impairs physiological nitric oxide (NO) activity promoting cardiovascular pathophysiological mechanisms. While inorganic nitrite and nitrate are now recognized as relevant sources of NO after their bioactivation by enzymatic and non-enzymatic pathways, thus lowering blood pressure, mounting evidence suggests that sodium nitrite also exerts antioxidant effects. Here we show for the first time that sodium nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 43 publications
5
29
0
7
Order By: Relevance
“…A variety of factors could affect the Km or velocity of XOR-mediated reactions using nitrite as a substrate, such as absence of oxygen [35], excess of NADH [36], absence of xanthine [36], and the activity of other enzymes that could scavenge reactive oxygen species [36]. Moreover, the concentration of XOR we utilized was probably in excess as compared with those found in rats [11], [37]. Therefore, the extent of nitrate-induced inhibition or XOR-mediated nitrite reductase activity in the tissues could be significantly different from that found in in vitro studies.…”
Section: Discussionmentioning
confidence: 95%
“…A variety of factors could affect the Km or velocity of XOR-mediated reactions using nitrite as a substrate, such as absence of oxygen [35], excess of NADH [36], absence of xanthine [36], and the activity of other enzymes that could scavenge reactive oxygen species [36]. Moreover, the concentration of XOR we utilized was probably in excess as compared with those found in rats [11], [37]. Therefore, the extent of nitrate-induced inhibition or XOR-mediated nitrite reductase activity in the tissues could be significantly different from that found in in vitro studies.…”
Section: Discussionmentioning
confidence: 95%
“…UNX–HS), comparable favourable effects were noted following L‐arginine and tempol treatments that also restored balance between ROS and NO , and by unilateral renal denervation that reduces sympathetic nerve activity . Studies conducted by another group showed that treatment with inorganic nitrite lowered oxidative stress and blood pressure dose‐dependently in two different rat models of renovascular hypertension, that is two‐kidney one‐clip (2K1C) and deoxycorticosterone (DOCA)–salt treatment .…”
Section: Therapeutic Value Of Stimulating the Nitrate–nitrite–no Pathwaymentioning
confidence: 93%
“…For example, beetroot due to its high inorganic nitrate content is considered as an adjuvant for the treatment of hypertension [32, 33]. In different animal models of hypertension, treatment with nitrate and/or nitrite, which boost NO levels, is effective in reducing elevated blood pressure [3437]. In addition, acute and short-term hypotensive effects of inorganic nitrates have been reported in several clinical studies [3841] as well as in meta-analyses [42, 43].…”
Section: No and H2s In The Pathogenesis Of Hypertensionmentioning
confidence: 99%